(untitled) (Texas Journal of Engineering and Technology, 2022)
This article is dedicated toIt is devoted to the analysis of energy consumption in everyday life and in industrial enterprises, as well as energy audit and methods of ensuring energy conservation. Calculations and developed measures on energy saving issues in industrial and industrial enterprises are also presented.